Pengaruh Derajat Penyebaran Lintas Fungsi Pemasaran (Marketing Cross-Functional) terhadap Kinerja Unit Bisnis Strategis, dengan Dinamisme Pasar sebagai Moderating Effect - Clara, Catharina (Jurnal Widya Manajemen & Akuntansi, 2005)
This research examines the link between the cross-functional dispersion of influence (marketing, sales, R &D, operation/production,and finance/accounting) on making marketing decisions and performance at the SBU level by considers market dynamism which may moderate the strength of this relationship. Additionally, it's explored the strength and the weaken factors of performance in manager insight. Market orientation come from the thought that company should realize that build consumer satisfaction is the primary of business goal by focused on consumer and competitor.